Vitamin Fortification of Milled Rice: A New Approach to Address Micronutrient Malnutrition - Camacho, Drexel H. (Animo Repository, 2018)
To address micronutrient deficiencies in the susceptible sector of society, it is recommended to fortify the commercial milled rice with vitamins using the new technique of fortification. The simple approach, which involves rice surface modification and vitamin absorption, is deemed economical compared to traditional fortification processes. Moreover, the susceptibility of losing vitamins due to washing processes is resolved in this improved grain fortification as ~90% of the vitamins are retained. The results shown in this study indicate the successful fortification of vitamins on rice and that fortification is more pronounced when the grain undergoes sonication process. As the staple food for an estimated 3 billion people worldwide, fortification of rice grains through sonication and adsorption allows vitamins to be delivered into the body regularly through the diet, which can be a potential approach towards a massive food fortification programs to address severe nutrient deficiencies in the population.